The scandal of the evangelical mind - Noll, Mark A. 1946- (Grand Rapids, MI Eerdmans, 1994)
Includes bibliographical references and index.
Keywords: Evangelicalism -- United States; Christianity -- United States -- forecasting; Christianity and culture